TINJAUAN PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH PADA MATERI PROGRAM LINIER SISW SMK NEGERI 1 PAINAN DENGAN PENERAPAN STRATEGI REACT - Titi Sumarni, Fahkrullah I Tama Umar (Menara Ilmu, 2018)
Learning mathematic at school should be include of problem solving, reasoning,interrelatedness communication and representation. One of main ability in learningmathematic is problem solving. It is very important, even it is called as heart ofmathematic. Thinking process in problem solving need ability of strategi organisation. Theability can train people to think critical, logic, and creative which is needed to face socialdevelopment.The abilitiy of problem solving have tight relationship with students’mathematic comprehension componet. In onther word we can say that students are able touse it in problem solving. One of appropriate strategy that can improve students’comprehension concept and problem solving is REACT. This is a learning strategy byusing contextual approch. This strategy consist of five steps first Relating, secondexperiencing, and then applying, and cooperating, the last is transferring. By applying thisstrategy, it is hope that it can improve students’ comprehension concept and problemsolving so that the objective of learning can be gained well. The purpose of this researchwas to know the improvement of students’ability in comprehension concept and problemsolving in linier program material of ten grade SMK Negeri 1 Painan students at techniccomputer network department (TKJ) by applying REACT strategy. The research isclassroom action research which consist of two cycles, each cycles involve four stages : (1)planning, (2) acting, (3) observing, and (4) reflecting.The instruments used to collect datawere observation cheklist and field note.It wa used to record and collect real informationof teaching and learning process in applying REACT strategy at XI TKJ of SMK Negeri 1Painan.To know the students’ ability inmathematic, the researcher gave a test at the end ofevery cycles. The result of this research show that, there is an improvement of students’comprehension concept and problem solving. At first cycle, the improvement was 87% and60% incomprehension concept and problem solving. At second cycle the improvementbecome 88% and 85%. Based on the result above we can conclude that the use of REACTstrategy could deepen students’ comprehension concept toward the material that they havebeen learned. Beside that the strategy could develop positifattitude such as respect eachother, responsibility, self confidence in giving opinion, because they learned in group.Kata Kunci : Pemahaman Konsep, Pemecahan Masalah, Strategi REACT